EVOLUTION AND GLOBAL TRENDS IN TECHNOLOGY USE FOR LANGUAGE TEACHING: IMPLICATIONS FOR EFL CLASSROOMS IN UZBEKISTAN (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This article looks at how educational technology has changed over time and how it's being used around the world in language teaching, especially for teaching English as a Foreign Language (EFL) in Uzbekistan. It talks about the history of these tools, new ideas, and how digital methods like blended learning, mobile apps and virtual classrooms are being used in practice. By taking inspiration from successful examples globally and considering the specific situation in Uzbekistan, the paper suggests some practical ways to improve language teaching with technology. The goal is to help teachers, policymakers, and those who design curriculums create more effective and inclusive language education in the country.